Neuroprotection by peripheral nerve electrical stimulation and remote postconditioning against acute experimental ischaemic stroke. (20th June 2015) - Xiao, Yao; Hafeez, Adam; Zhang, Ying; Liu, Shimeng; Kong, Qingtao; Duan, Yunxia; Luo, Yumin; Ding, Yuchuan; Shi, Huaizhang; Ji, Xunming
Abstract : Objective: Local electrical stimulation (ES) was reported to protect the brain during ischaemic injury, while the protective effect of limb remote ischaemic postconditioning (RIPostC) was confirmed. The aim of this study was to explore whether remote peripheral nerve ES exerted neuroprotection and whether this procedure shared the same neuroprotective mechanism underlying RIPostC. Methods: Stroke in Sprague-Dawley rats was induced by distal middle cerebral artery occlusion (dMCAO). Rats were divided into five groups: dMCAO, RIPostC, ES, nerve resection (NR) + ES and RIPostC+ES. Twenty-four hours after reperfusion, rats were examined for neurobehavioural function, including forelimb fault placing test, Ludmila Belayev 12 score test, and infarct volume. The expression of Bcl-2 and cleaved-caspase-3 in ischaemic cortex was assessed by Western blot. Results: In forelimb fault placing test, as compared to the highest score in the stroke-only group, RIPostC, ES and RIPostC+ES groups showed a significantly ( P < 0.01) lower score. The results were similar for the Ludmila Belayev 12 score test. The infarct volume of the treatment groups also exhibited significant ( P < 0.01) reduction as compared to the stroke-only group. The volume of infarct tissue in the combination of RIPostC+ES was significantly less than RIPostC and ES alone ( P < 0.05). Furthermore, NR blocked the ES's protection ( P < 0.05) as compared to the ES group by using above-mentioned methods. Bcl-2 was upregulated, while cleaved-caspase-3 was downregulated in the experimental groups as compared to the control group. No difference was found among the experimental groups. Discussion: Peripheral nerve ES appears to have a neuroprotective effect in a rat dMCAO model. This effect may indicate a neural protective mechanism underlying beneficial effect of RIPostC.